2006
DOI: 10.1536/ihj.47.821
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Abciximab Combined With Dalteparin or Unfractionated Heparin in High-Risk Percutaneous Coronary Intervention in Acute Myocardial Infarction Patients

Abstract: SUMMARYThe purpose of this study was to determine the clinical outcomes of abciximab combined with the low molecular weight heparin (LMWH), dalteparin, in high-risk percutaneous coronary intervention (PCI) patients with acute myocardial infarction (AMI). A total of 140 high-risk PCI patients with AMI were divided into 2 groups: unfractionated heparin (UFH) with abciximab (group I: 70 patients, 58.7 ± 10.5 years), and dalteparin with abciximab (group II: 70 patients, 59.6 ± 9.8 years). Major adverse cardiac eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…One nonrandomized study compared dalteparin with UFH in STEMI patients undergoing PCI and showed a neutral result (LOE 2). 437 …”
Section: Consensus On Sciencementioning
confidence: 99%
“…One nonrandomized study compared dalteparin with UFH in STEMI patients undergoing PCI and showed a neutral result (LOE 2). 437 …”
Section: Consensus On Sciencementioning
confidence: 99%
“…Kim et al 34 have suggested that tirofiban in combination with dalteparin in patients with acute coronary syndrome can significantly lower the incidence of MACEs compared with UFH plus tirofiban. In our study, no significant differences in the incidence of MACEs or stent thrombosis were found between the two groups ( P =0.81 and 0.87).…”
Section: Discussionmentioning
confidence: 99%
“…Data for other LMWHs such as dalteparin in PCI has been limited [23,24]. A recent study which directly compared dalteparin (70 IU/kg with GP IIb/IIIa inhibitors and 100 IU/kg dalteparin without it) with UFH, showed no significant difference in the composite of death, MI, target vessel revascularization, or bailout GP IIb/IIIa inhibitor at hospital discharge (13.7% in the UFH group and 13.1% in the dalteparin group) [25].…”
Section: Low-molecular Weight Heparinsmentioning
confidence: 99%